Investigating the relationship between brand experience, brand authenticity, brand equity, and customer satisfaction: Evidence from Vietnam - Van- Dat Tran; Ngoc Truc Thao Nguyen (Cogent Business & Management, 2022)
The purpose of this research is to investigate the relationship between brand experience, brand authenticity, brand equity, and how those factors effect on customer satisfaction. The measurement model and the conceptual model depicting hypothesized relationships were evaluated based on responses from 295 customers using confirmatory factor analysis and structural equation modeling, accordingly. By empirical analysis, the study developed a new model presenting positive significant relationships among brand experience, brand authenticity, and brand equity and customer satisfaction. Especially, it is a valuable contribution to branding subject that brand experience positively affects the authenticity of the global brand. Drawing from the study's findings, managerial implications are discussed. Customers' experience about the global brand can increase the authenticity and equity of the brand in the market as well as understandings of what consumers feel about products/services in order to improve their satisfaction. Besides, this study experimented with both concepts and found a positive significant relationship between brand experience and brand authenticity. The more customers use and feel the products/services, the more authentic values that the brand has.
Keywords: M30; M31; M37; 650; brand equity; customer satisfaction; brand authenticity; brand experience